The impact mechanism of China’s carbon emission trading policy on industrial energy efficiency under multiple innovation approaches - Li, Jinqiu; Huang, Dechun (Frontiers in Energy Research, 2023)
Under the “dual carbon” background, carbon emission trading policy, as an important means of environmental regulation for energy conservation, emission reduction and green development, has a very important impact on energy efficiency. We take China’s pilot carbon trading policy, which began in 2013, as an example, and the energy efficiency of industrial enterprises from 2008 to 2019 as a study sample. In this paper, the single factor industrial energy efficiency (ISE) and the green total factor industrial energy efficiency (IGTE) in China are both included in the influence category of carbon emission trading. The SUPER-EBM method is used to measure IGTE. The direct effects of carbon emission trading policy on the two types of industrial energy efficiency are investigated by Difference-in-difference model combined with stepwise regression method. The dynamic effects are studied by event study method. In order to verify how the “Porter effect” plays a role in this process, this paper examines the influence paths of five important innovation-related intermediate mechanisms. The study find that after a series of robustness tests, such as parallel trend test, placebo test, changing the time window frame and adding control variables, carbon emission trading policy significantly improved the two energy efficiency. The effect of carbon trading policy gradually increased and reached its maximum in the fifth year, but then began to decline. Under multiple innovation approaches, innovation environment level and innovation protection intensity can significantly improve the two energy efficiency. Green innovation intensity and breakthrough innovation intensity improved ISE. The overall level of enterprise innovation improved IGTE. Heterogeneity analysis shows that carbon trading policy has a greater impact on the eastern region, but a smaller impact on the central and western regions. This paper provides differentiated policy inspiration for the overall promotion of China’s national carbon market in the future.